2016
DOI: 10.15561/20755279.2016.0307
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Biorhythm (Physical Cycle) and Sports Performance in Women's Basketball

Abstract: Abstract.Purpose: the purpose of this study was to verify if there is any significant difference between body fat assessment by calculating body mass index and by using bioelectrical impedance analysis. Materials: subsequently we determined the ratio between body fat and muscular mass percentage in a sample of 156 university girl students. Results: BMI and muscle mass percentage seem to have similar variance and trends, while body fat exceeded in numbers and percents the highest levels of BMI. While by calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Our observations and data from other researchers (Shafiee, Rahim, Hakime & Vahid, 2016; show that a basketball player has a position that the defender holds in relation to his character and opposition. It is located at different distances depending on the game situation.…”
Section: Discussionsupporting
confidence: 68%
“…Our observations and data from other researchers (Shafiee, Rahim, Hakime & Vahid, 2016; show that a basketball player has a position that the defender holds in relation to his character and opposition. It is located at different distances depending on the game situation.…”
Section: Discussionsupporting
confidence: 68%
“…Player 2 has a period of fluctuations in game performance of 32 days. Based on the literature data on the psycho-physiological features of people with different biorhythm periods [23,24,25], it can be concluded that this athlete's general condition, and, consequently, his competitive performance, depends on the psychological state, on his inner world. The obtained data are in line with our previous studies [15], which showed that in qualified basketball players, the game performance correlates with the values of the intellectual biological rhythm.…”
Section: Discussionmentioning
confidence: 99%